2023
DOI: 10.3390/inorganics11030131
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Artificially Synthesized Granitic Residual Soil-Supported Nano Zero-Valent Iron (Gr-nZVI) as Effective Heavy Metal Contaminant Adsorbent

Abstract: Supported nano zero-valent iron is receiving great attention nowadays due to its effectiveness in treating heavy metal pollutants. Therefore, this study aimed to investigate the effectiveness of granitic residual soil-supported nano zero-valent iron (Gr-nZVI) for the removal of the heavy metals Pb2+, Cu2+, Co2+, Cd2+ Ni2+ and Zn2+ in mixture solutions under different experimental conditions of batch equilibrium tests. In this study, Gr-nZVI was successfully synthesized by using the chemical reduction of Ferric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The results indicated that the surface diffusion process could remove Ni 2+ faster in the early stage of the reaction. As the reaction proceeded, the reaction rate was limited to a certain extent due to the high resistance of the boundary layer, which led to the slowing down of the reaction rate and eventually to the equilibrium [34]. The fitted plots showed that none of the fitted straight lines passed through the origin, indicating that the adsorption rate of Ni 2+ by nZVI@ATP was limited by other factors such as surface diffusion and surface adsorption in addition to the main intra-particle diffusion.…”
Section: Kineticsmentioning
confidence: 99%
“…The results indicated that the surface diffusion process could remove Ni 2+ faster in the early stage of the reaction. As the reaction proceeded, the reaction rate was limited to a certain extent due to the high resistance of the boundary layer, which led to the slowing down of the reaction rate and eventually to the equilibrium [34]. The fitted plots showed that none of the fitted straight lines passed through the origin, indicating that the adsorption rate of Ni 2+ by nZVI@ATP was limited by other factors such as surface diffusion and surface adsorption in addition to the main intra-particle diffusion.…”
Section: Kineticsmentioning
confidence: 99%
“…Hydrophobic supports also extend the reactivity of nanoparticles and enable the adsorption of hydrophobic contaminants like PCBs onto the nZVI surface. Materials such as phyllosilicate minerals [225], granitic residual [226], silica [227], activated carbon [228], zeolites [229], biochar [230] or polymer membranes have been utilized as supports for nZVIs. Immobilization of nZVIs on these supports can be achieved through carboxyl, hydroxyl, or amine groups serving as chelating sites.…”
Section: Fixed Supportmentioning
confidence: 99%